Gastric volvulus and wandering spleen in Pitt–Hopkins syndrome: first paediatric case report - Vasta, Gabriele; Angotti, R.; Contini, G.; Perrotta, M. L.; Molinaro, F.; Tarallo, L.; Plessi, C.; Briganti, V. (Frontiers in Pediatrics, 2025)
BackgroundAcute gastric volvulus is a rare condition in children, and delayed diagnosis may lead to gastric ischemia, perforation, or even death. It is sometimes associated with a wandering spleen, a condition in which the spleen migrates from its normal anatomical position due to the absence of fixation ligaments. We report the first known case of a patient with Pitt–Hopkins syndrome (PTHS) presenting with simultaneous acute gastric volvulus and a wandering spleen.Case reportA 6-year-old male with PTHS was urgently referred for acute abdominal pain and a 24 h history of non-bilious and non-bloody emesis. The x-ray showed a massive gastric dilatation, and an upper gastrointestinal series (UGI) revealed a gastric outlet obstruction. An emergency laparoscopy revealed a gastric mesoaxial volvulus with a hypotonic wall with no sign of ischemia or perforation associated with a wandering spleen. Gastropexy was performed by anchoring the gastric greater curvature to the anterior abdominal wall, covering the spleen in a good position in the left upper abdomen, completely covered by the gastric fundus. The patient made an uneventful recovery and was completely asymptomatic.ConclusionTo our knowledge, this is the first reported case of simultaneous gastric volvulus and wandering spleen in a patient with PTHS. Laparoscopic gastropexy is a straightforward and effective procedure that combines the advantages of previously described surgical techniques.